Breaking the Jaws of Silence : Sixty American Poets Speak to the World - Wolpe, Sholeh (Book collections on Project MUSE., 2013)
Sholeh Wolpe is the author of three collections of poetry including Keeping Time with Blue Hyacinths and Rooftops of Tehran , and she is the editor of The Forbidden: Poems from Iran and Its Exiles and a regional editor of Tablet & Pen: Literary Landscapes from the Modern Middle East . Her books of translations include Sin: Poems of Forugh Farrokhzad , which was awarded the Lois Roth Persian Translations Award in 2010, and a Persian translation of Walt Whitman's Song of Myself.